The Fallacies of States' Rights - SOTIRIOS A. BARBER (Harvard University Press, 2013)
The statesâ€™ rights debate is Americaâ€™s oldest constitutional debate. Every issue in the campaign to ratify the Constitution was connected to the question of the future of the states in the proposed federal union. Re sis tance to national power in the name of statesâ€™ rights brought the nation close to civil war on two occasions before fi ring started on Fort Sumter in 1861. Fearing that the Civil War Amendments to the Constitution would â€œfetter and degrade the State governments,â€ the Supreme Court nullifi ed all but the amendmentsâ€™ minimal promise for generations after the war. The scope of national power relative to the states was a major part of the confl icts of the Progressive Era and the New Deal. Expressing concern for the statesâ€™ traditional control of the public schools, the Supreme Court abandoned the promise of equal educational opportunity less than two de cades after the desegregation decision in 1954. Claims of â€œstatesâ€™ rightsâ€ have played an important role in opposition to the Courtâ€™s decisions on school prayer, the treatment of criminal defendants, abortion, and gay rights. â€œStatesâ€™ rightsâ€ was a battle cry of the strategy that transformed the Republican Party from the party of Lincoln to the party of Reagan. A dramatic if limited return to statesâ€™ rights was the signature achievement of the Rehnquist Court. At this writing statesâ€™ rights is the battle cry against the Patient Protection and Affordable Care Act of 2010 (â€œObamacareâ€). And though it has no real connection to statesâ€™ rights, something called â€œcompetitive federalismâ€ is part of the present campaign of corporate forces to deregulate the nationâ€™s economic life. Yet in most of these cases observers could wonder whether statesâ€™ rights was the most important issue. Did Thomas Jefferson and Alexander Hamilton disagree mostly over states rights or over the merits of an urbanindustrial order? Was the Civil War fought for statesâ€™ rights or for slavery?Do pro- life forces oppose Roe v. Wade for taking an issue from the states or for legalizing abortion? Are opponents of the federal minimum wage indifferent to state minimum wages? Would critics of â€œObamacareâ€ remain silent if the states enacted similar mea sures? Behind these questions is a larger question of whether anything general can be said about what is really at stake in the federalism debate. If there is a bigger issue behind the federalism debate, what might it be? And if the federalism debate is a mask or a proxy for other issues, is anyone really interested in federalism or statesâ€™ rights?